ASSESSING THE VULNERABILITY OF GLOBAL VALUE CHAINS TO GLOBAL ECONOMIC RISKS - MYTSENKO, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of this paper is to assess the vulnerability of global value chains (GVCs) to macroeconomic shocks, in particular, the 2008 Global Financial Crisis (GFC), trade tensions and the COVID-19 pandemic. The paper analyses how these events have led to structural changes in global trade, including a significant reduction in exports and disruptions to logistics chains. Dynamic regression modelling is applied based on trade data and value chain indicators (OECD) for the period 2007–2020. The study identifies the impact of GDP growth rates of key economies (USA, EU, China) and the time factor on GVC indicators (reimported domestic value added, foreign value added in gross exports, gross imports of final and intermediate goods) in different regions (Japan, Korea, USA, China, EU, NAFTA, ASEAN). The results showed that the indicator of gross imports of final products is the most sensitive to macroeconomic dynamics, demonstrating a high explanatory power of the models. Complex relationships were also revealed, in particular, the negative impact of China’s own GDP growth on its reimports, which indicates import substitution processes. The results emphasize the structural interdependence of world economies and confirm the high vulnerability of GVCs to global crises. The highest explanatory power was achieved for the model of gross imports of final products, which indicates a strong and direct dependence of demand for final products on the macroeconomic dynamics of the world’s largest economies and long-term trends (time factor). Reimported domestic value added and foreign value added in exports also showed significant sensitivity to the selected factors, although with less universal statistical significance. For example, China’s GDP growth had a significant negative impact on its own re-imports and foreign value added, which may indicate a successful import substitution strategy and strengthening of domestic production capacity. Thus, global value chains have confirmed their structural vulnerability to powerful economic and geopolitical shocks. Modeling has clearly shown that the macroeconomic dynamics of key global economies (the US, EU, China) are a decisive factor for GVC integration indicators. The continued functioning and restoration of stability in GVCs, which is threatened by military aggression against Ukraine, requires accelerated digitalization and, likely, further reconfiguration to increase resilience (regionalization, chain shortening, supplier reliability improvement).